Self‐Assembly of Nanostructured, Complex, Multication Films via Spontaneous Phase Separation and Strain‐Driven Ordering. (12th November 2012) - Wee, Sung Hun; Gao, Yanfei; Zuev, Yuri L.; More, Karren L.; Meng, Jianyong; Zhong, Jianxin; Stocks, George M.; Goyal, Amit
Abstract Spontaneous self‐assembly of a multication nanophase in another multication matrix phase is a promising bottom‐up approach to fabricate novel, nanocomposite structures for a range of applications. In an effort to understand the mechanisms for such self‐assembly, complimentary experimental and theoretical studies are reported to first understand and then control or guide the self‐assembly of insulating BaZrO3 (BZO) nanodots within REBa2Cu3O7–δ (RE = rare earth elements including Y, REBCO) superconducting films. The strain field developed around BZO nanodots embedded in the REBCO matrix is a key driving force dictating the self‐assembly of BZO nanodots along REBCO c‐axis. The size selection and spatial ordering of BZO self‐assembly are simulated using thermodynamic and kinetic models. The BZO self‐assembly is controllable by tuning the interphase strain field. REBCO superconducting films with BZO defect arrays self‐assembled to align in both vertical (REBCO c‐axis) and horizontal (REBCO ab‐planes) directions result in the maximized pinning and Jc performance for all field angles with smaller angular Jc anisotropy. The work has broad implications for the fabrication of controlled self‐assembled nanostructures for a range of applications via strain‐tuning.